Comportamiento agronómico y productivo de la línea promisoria de arroz (Oryza sp.) L-37 en la zona de Yaguachi, provincia del Guayas - Hernández Ronquillo, María Isabel (2024)
Rice (Oryza sativa L.), is the staple food in developing countries, with growing global demand due to increasing population and consumption patterns. In Yaguachi, rice cultivation is crucial according to studies and projects. The L-37 rice line is relevant for its high productivity and tolerance to pests and diseases. This research is carried out by field/laboratory with inferential descriptive statistics, the objective was to determine the agronomic and productive behavior of the promising line of rice L-37, which led to the use of a methodology of two treatments, L-37 and SFL-11 in three replications. The following variables were recorded: Plant height (cm), number of tillers, number of panicles, length of panicles (cm), number of total grains per panicle, length (mm) and width (mm) of grains with and without shells; and yield (kg/ha). A non-parametric design of Kruskal Wallis analysis was performed. Regarding the results, the promising L-37 line presented a lower panicle number, obtaining a value of 20.04, compared to the SFL-11 variety (control) that presented 21.46 panicles. The L-37 line presented a lower percentage (17.92%) of span grains, compared to the SFL-11 commercial control variety, which consists of a higher percentage of span grains (21.91%). It is revealed that the promising line L-37 has a planting distance of 26.4 cm between plants, while the commercial variety SFL-11 has a slightly greater distance of 28.23 cm. While there are similarities in the agronomic characteristics of the SFL-11 variety and the promising L-37 line, it is the latter that really shines in terms of yield, producing an impressive range of 6.5 to 7 tons per hectare. This is particularly notable considering that the SFL-11 control variety exhibits similar agronomic behaviors. In their study Reyes et al. (2022) mentions something fundamental about genetics in the continuous improvement of crop quality, of developing new lines that boost agricultural production in Ecuador.